2016
DOI: 10.18632/oncotarget.14207
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical assesement of survivin and XIAP as prognostic biomarkers and therapeutic targets in gastroenteropancreatic neuroendocrine neoplasia

Abstract: Gastroenteropancreatic neuroendocrine neoplasms (GEP-NEN) represent a rare and heterogenous tumor entity. Importantly, the highly proliferative subgroup of neuroendocrine carcinoma (GEP-NEC) is characterized by high resistance to conventional chemotherapy. Consequently, there is an urgent need to identify novel therapeutic targets, especially for GEP-NEC. Thus, we focused on Inhibitor of apoptosis protein (IAP) family members survivin and XIAP that orchestrate inhibition of apoptosis, induce resistance against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 43 publications
1
30
0
Order By: Relevance
“…Of note, in previous studies using monoclonal as well as aforementioned polyclonal antibodies, we failed to detect survivin splice variants on protein levels (55). Importantly, the specificity of the antibody that we used in our study was also confirmed in knock down experiments that we recently performed (30).…”
Section: Svv (Cyt)-center Svv (Cyt)-invasion ----------------------supporting
confidence: 73%
See 3 more Smart Citations
“…Of note, in previous studies using monoclonal as well as aforementioned polyclonal antibodies, we failed to detect survivin splice variants on protein levels (55). Importantly, the specificity of the antibody that we used in our study was also confirmed in knock down experiments that we recently performed (30).…”
Section: Svv (Cyt)-center Svv (Cyt)-invasion ----------------------supporting
confidence: 73%
“…Formalin-fixed and paraffin embedded (FFPE) tumor specimens were obtained from the Institute of Pathology, University Hospital Duesseldorf. Tissue microarray (TMA) construction was performed as recently described (30). If available two cylinders of 1.0 mm diameter were taken from the tumor center and invasion front, one from tumor surrounding non-malignant mucosa and one from a lymph node metastasis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two µm thick sections were cut from each TMA block and mounted on superfrost microscope slides. Immunohistochemical staining was performed as recently described (23,24). Two independent investigators (LD and LMJ) blinded to clinicopathological information evaluated the expression of survivin and XIAP using the immunoreactivity score (IRS) according to Remmele (25).…”
Section: Methodsmentioning
confidence: 99%